2015
DOI: 10.1007/s00394-015-1047-2
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal prebiotic fibre intake mitigates some detrimental metabolic outcomes of early overnutrition in rats

Abstract: Postnatal consumption of OFS by rats raised in SL was able to attenuate body fat and glycaemia to levels seen in NL rats. OFS appears to influence satiety hormone and gut microbiota response similarly in overnourished and control rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 69 publications
1
18
0
1
Order By: Relevance
“…In some cases, the administration of specific dietary components improved host health and also increased the Akkermansia population. Such compounds include polyphenols [19,47,48], fructo-oligosaccharide [49,50], conjugated linoleic acid [51], oat bran [52], type 2 resistant starch from high-amylose maize [53], fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) [54], whole grain barley [55] and polyamines [56,57], red pitaya [58] Bifidobacterium animalis subsp lactis LMG P-28149 [59], maize-derived non-digestible feruloylated oligo-and polysaccharides [60], amongst others. Interestingly, medicinal herbs (Flos Lonicera and fermented Rhizoma Atractylodis Macrocephalae) as well as fungi (Ganoderma lucidum) that are traditionally considered in Asian culture as medicine [61e63], also increased the proportion of Akkermansia with a concomitant beneficial effect on host metabolism.…”
Section: Modulation By Dietmentioning
confidence: 99%
“…In some cases, the administration of specific dietary components improved host health and also increased the Akkermansia population. Such compounds include polyphenols [19,47,48], fructo-oligosaccharide [49,50], conjugated linoleic acid [51], oat bran [52], type 2 resistant starch from high-amylose maize [53], fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) [54], whole grain barley [55] and polyamines [56,57], red pitaya [58] Bifidobacterium animalis subsp lactis LMG P-28149 [59], maize-derived non-digestible feruloylated oligo-and polysaccharides [60], amongst others. Interestingly, medicinal herbs (Flos Lonicera and fermented Rhizoma Atractylodis Macrocephalae) as well as fungi (Ganoderma lucidum) that are traditionally considered in Asian culture as medicine [61e63], also increased the proportion of Akkermansia with a concomitant beneficial effect on host metabolism.…”
Section: Modulation By Dietmentioning
confidence: 99%
“…abundance in the intestine. In animal studies, the administration of any kind of nutrients that increased the amount of Akkermansia muciniphila improved host physiological conditions consequently (23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soy protein and threonine can be used instead of mucin, and a certain amount of N-acetylglucosamine, N-acetylgalactosamine, and glucose can be added to form a mixed medium to cultivate A. muciniphila, and the biomass of which is not significantly different with that grown in BPM 13,34 . In addition, the study found that by adding fructooligosaccharides [35][36] , metformin [37][38] , polyphenols [39][40][41][42] , probiotics 43 and fish oil unsaturated fatty acids 44 diabetes. The main metabolite of A. muciniphila is a short-chain fatty acid.…”
Section: Effect Of Different Media On a Muciniphila Biomassmentioning
confidence: 99%